Awareness of sudden unexpected death in epilepsy among parents of children with epilepsy in a tertiary center - TÜRKDOĞAN, DİLŞAD; SAVE, DİLŞAD (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
Objective: Sudden unexpected death in epilepsy (SUDEP) is the second leading neurological cause of potential years of lifelost after stroke. Despite growing numbers of studies on social aspects of epilepsy, there is a paucity of research on the awareness of SUDEP among the parents of children with epilepsy (CWE), especially in Turkey. In this study, we aimed to evaluate the knowledge of parents of the CWE regarding SUDEP in the tertiary setting. Material and methods: A total of 146 parents (108 female) aged 19 to 55 years (median age:34) of CWE were included at Marmara University, School of Medicine, Department of Pediatric Neurology outpatient clinic between May 2018 and September 2018. A total of 30 multiple-choice questions and a written survey were administered, which consisted of three sections. In the first section, the sociodemographics of parents and CWE were questioned. In the second section, the severity of epilepsy was evaluated. In the third section, the knowledge level and awareness of parents of CWE were assessed. Results: Of 146 parents, only 16.6% previously heard about SUDEP, while 45% of them heard from their relatives. The presence of prior knowledge of SUDEP was associated with the presence of prolonged postictal confusion and longer duration of epilepsy (p < 0.05). Ninety-seven (66%) parents desired to be informed about SUDEP, while 76 (54.7%) of them agreed that this information should be given at the time of diagnosis. The degree of anxiety in parents regarding death of epilepsy-related causes was significantly related with prolonged postictal confusion (p < 0.001) and using three or more antiepileptic drugs (p = 0.005). Conclusion: Our data suggest that knowledge about SUDEP among parents with CWE found inadequate in Turkey. There should be much effort to inform parents and caregivers in epilepsy clinics on SUDEP, which may help to reduce the associated risk factors. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Sudden death; Epilepsy; Child; Parents; Knowledge; MORTALITY TASK-FORCE; RISK-FACTORS; INTERNATIONAL LEAGUE; PREMATURE MORTALITY; AMERICAN EPILEPSY; INCOME COUNTRIES; SUDEP; EXPERIENCES; PROVISION; COMMUNITY